Study of the relationship between the hyperpyrexia syndrome and the number of the bacteria in the air of the pogpens - YU Xu-ping; HE Shi-cheng; WU Hai-bo; JIN Jun-jie; ZHU Jun-li (浙江大学学报. 农业与生命科学版, 2005)
In the summer of 2001, a disease called “hyperpyrexia syndrome”, the basic feature of which are hyperpyrexia, wheeze and hyperaemia of the skin, broke out in Zhejiang, Shanghai and their neighboring areas. It caused great loss in the pig industry. However, up to now, the pathogen(s) of the disease have not yet been identified. In order to investigate the relationship between the airborne bacteria and hyperpyrexia syndrome, we measured the number of the bacteria in the air in hogpens with different degrees of severity of the disease in Zhejiang Province. Results showed that there was a positive relationship between incidence of the disease and the number of the bacteria in the air of the pogpens.